Karakteristik Hasil Ultrasonografi Payudara pada Program Deteksi Dini Kanker Payudara di Kota Solo - Rachmi Fauziah Rahayu; Rospitasari Rospitasari; Adam Prabata; Luths Maharina (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Breast cancer is the most common cancer found in women worldwide, including Indonesia. Breast cancer was the most second cancer-related death in Indonesia with 22,000 mortality cases in 2018. The high mortality rate is worsened by the fact that 80% breast cancer cases in Indonesia was detected when its already in advanced stage, so the morbidity and mortality rate will be high. In response to those problems, we held a community service activity which comprises counselling of breast self-examination (BSE) methods and free breast ultrasonography examination. Counselling was held to improve knowledge and awareness regarding breast cancer, whereas free breast ultrasonography examination was held to give access of one of breast cancer early detection method for community. We found 9 people (16.4% of all participants) who had breast lesion and 11 people (20.0% of all participants) who had lymph node involvement. The mean of age of the community service participants was 47.4 years old, so our community service program is right on the target, matching with the riskiest age group of breast cancer. Improving knowledge and awareness regarding the importance of early detection for breast cancer, then contributing to add breast ultrasonography examination data in Indonesia, especially at Solo, were the aim for this community service program.